2010
DOI: 10.1007/s11947-010-0357-x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Enzymatic Hydrolysis of Visceral Waste Proteins of Yellowfin Tuna (Thunnus albacares)

Abstract: Fish protein hydrolysate was produced from the viscera of yellowfin tuna (Thunnus albacares). Hydrolysis conditions (enzyme activity, temperature, and time) were optimized using response surface methodology. A factorial design was applied to minimize enzyme utilization and modeling of degree of hydrolysis (r 2 =0.94). Lack-of-fit test revealed a non-significant value for the model, indicating that the regression equation was adequate for predicting the degree of hydrolysis under any combination of the variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 30 publications
8
61
1
7
Order By: Relevance
“…This means that the hydrolysis conditions play a dominant role in the peptide bond cleavage in the protein substrate, which concurs with other observations (Adler-Nissen, 1986;Bhaskar et al, 2008;Ovissipour et al, 2012). The largest F-value (85.84) for time indicated that it was the most important linear variable influencing the values of TCA index, followed by initial pH, temperature and substrate concentration.…”
Section: Optimization Of Hydrolysis Parameterssupporting
confidence: 90%
See 1 more Smart Citation
“…This means that the hydrolysis conditions play a dominant role in the peptide bond cleavage in the protein substrate, which concurs with other observations (Adler-Nissen, 1986;Bhaskar et al, 2008;Ovissipour et al, 2012). The largest F-value (85.84) for time indicated that it was the most important linear variable influencing the values of TCA index, followed by initial pH, temperature and substrate concentration.…”
Section: Optimization Of Hydrolysis Parameterssupporting
confidence: 90%
“…The predicted protein efficiency ratio (PER) was calculated from the amino acid composition based on equations developed by Alsmeyer et al (1974) and Lee et al (1978). These equations have also been applied by some researchers to predict protein hydrolysates (Grazziotin et al, 2006;Ovissipour et al, 2012). The predicted biological value (BV) was calculated using the regression equation developed by Morup and Olesen (1976).…”
Section: Measurement Of Chemical Compositionmentioning
confidence: 99%
“…The cleavage of the peptide bonds of the protein substrate has been found to be markedly influenced by the conditions under which the substrate is hydrolyzed with bacterial proteases (Wang and Xu, 2007;Zhu and Row, 2011;Ovissipour et al, 2012). In this study, after the proteases were produced from the B. subtilis, the cleavage of the peptide bonds of the blood cells was influenced by the degradation conditions.…”
Section: Optimization Of the Degradation Conditions Through Response mentioning
confidence: 81%
“…Empirical models have also been used in both polynomial equations using the response surface methodology (RSM) [22][23][24][25][26] and artificial neural networks (ANN) [27][28][29] applied to fish protein hydrolysis. Multivariable polynomial equations allowed for the simultaneous study of multiple factors affecting the hydrolysis process.…”
Section: Introductionmentioning
confidence: 99%